Interview with Willi Jäger - Kirkilionis, Markus; Krömker, Susanne; Rannacher, Rolf; Tomi, Friedrich; Brueggemann, Aminia M. (Trends in nonlinear analysis, 2003)
A while ago, we had the idea of publishing a book about our conference “Trends in Nonlinear Analysis, TiNA 2000”. As the book will be published in honor of the 60th birthday of Willi Jäger, we decided to include an interview that would highlight his biography as well as his view of mathematics. We tried to find good questions. On April 30, 2000, the interview was conducted spontaneously and without prior knowledge of the questions. The interview is roughly organized as follows: His own biography, the current situation of mathematics, science organization, and the representation of mathematics in the public eye, and finally, perspectives, and visions.
Gesehen am 15.06.2021